2021
DOI: 10.3390/biom11121787
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Arrangement Is Shown to Differ in Coexisting Phases of Aqueous Two-Phase Systems

Abstract: Analysis by attenuated total reflection–Fourier transform infrared spectroscopy shows that each coexisting phase in aqueous two-phase systems has a different arrangement of hydrogen bonds. Specific arrangements vary for systems formed by different solutes. The hydrogen bond arrangement is shown to correlate with differences in hydrophobic and electrostatic properties of the different phases of five specific systems, four formed by two polymers and one by a single polymer and salt. The results presented here su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 37 publications
5
10
0
Order By: Relevance
“…We found that the best and most reliable fits gave peak frequencies within the error band of values from literature [ 22 ], which were therefore fixed for all later fitting routines. These values, which we confirmed earlier [ 17 , 20 ], are 3080 cm −1 , 3230 cm −1 , 3400 cm −1 , and 3550 cm −1 , represented by respectively. The fit includes the four Gaussian expressions identified by the subscript, with baseline B and normalization by A to the measured total amplitude, where is the standard deviation of each Gaussian component, and is the amplitude contribution of each: …”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…We found that the best and most reliable fits gave peak frequencies within the error band of values from literature [ 22 ], which were therefore fixed for all later fitting routines. These values, which we confirmed earlier [ 17 , 20 ], are 3080 cm −1 , 3230 cm −1 , 3400 cm −1 , and 3550 cm −1 , represented by respectively. The fit includes the four Gaussian expressions identified by the subscript, with baseline B and normalization by A to the measured total amplitude, where is the standard deviation of each Gaussian component, and is the amplitude contribution of each: …”
Section: Methodssupporting
confidence: 91%
“…This method may not therefore be used for many proteins such as serum albumin or lysozyme. We recently used ATR-FTIR spectroscopy to show that the solvent features of water are strongly correlated with hydrogen bond arrangement in solutions of various compounds [ 17 , 18 , 19 , 20 , 21 , 22 ]; here we use it to explore the rearrangement of hydrogen bonds in aqueous solutions of several globular proteins.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the best and most reliable fits gave peak frequencies within the error band of values from literature [22], which were therefore fixed for all later fitting routines. These values, which we confirmed earlier [17,20], are 3080 cm -1 , 3230 cm -1 , 3400 cm -1 , and 3550 cm -1 , represented by 𝜇𝜇 1−4 respectively. The fit includes the four Gaussian expressions identified by the subscript, with baseline B and normalization by A to the measured total amplitude, where 𝜎𝜎 𝑖𝑖 is the standard deviation of each Gaussian component, and 𝑎𝑎 𝑖𝑖 is the amplitude contribution of each:…”
Section: Analysis Of Atr-ftir Spectrasupporting
confidence: 89%
“…Previously reported solvent properties of water [20], such as solvent dipolarity/polarizability, π*, solvent H-bond donor acidity, α, and solvent H-bond acceptor basicity, β, correlate strongly with the fractional contributions of subpopulations of water. This approach was used successfully to analyze the coexisting phases of several aqueous two-phase systems [17]. We apply the same model here for the analysis of water in solutions of different globular proteins.…”
Section: Analysis Of Atr-ftir Spectramentioning
confidence: 99%
See 1 more Smart Citation